Politeness Strategies used by the First Semester EFL Students in Online Classroom Interaction at UNISMUH Makassar - La Sunra; Sri Arna Nengsi; Abd. Halim (Celebes Journal of Language Studies, 2022)
This research highlights the politeness strategies used by the first semester EFL students in online classroom interaction at UNISMUH Makassar. The objectives of this research were: (1) find out the types of politeness strategies used by the first semester EFL students in online classroom interaction (2) examine the reasons why the first semester EFL students use politeness strategies in online classroom interaction (3) explore the lecturers’ perception about the politeness strategies used by the first semester EFL students in online classroom interaction. This research used descriptive-qualitative method. The subject of the research consisted of three classes in the first semester English Education Department at UNISMUH Makassar. The data were collected by using observation checklist, audio recorder and interview guides. The result of this research revealed that (1) there were four politeness strategies used by the first semester EFL students in online classroom interaction at UNISMUH Makassar, they were bald on record strategy, positive politeness strategy, and negative politeness strategy and off record politeness strategy. From a total of 220 utterances, the most frequently used strategy was bald on record politeness strategy (109 times), positive politeness strategy (43 times), negative politeness strategy (65 times) and off record (3 times), (2) the reasons why students used politeness strategy were to make comfortable communication, create harmony, mutual respect, make the class calm and peaceful, and build intimacy and solidarity to avoid disputes and misunderstandings, (3) In lecturers' perceptions, in order to be polite in online classroom interaction, the first semester EFL students used greeting, saying farewell, apologizing, permission, give deference and good cooperation in class. The lecturers highly appreciate and have a good perspective on the politeness strategies used by the EFL students in online classroom interactions.